Outcome of dorsal metatarsal artery perforator flap for coverage of soft tissue defect of dorsal distal foot and toes - Das, Achintya Kumar; Alam, M. Touhid; Nahar, Umme R. M. M.; Haider, Tazia; Sultana, Mahima; Rony, Nahid S. (International Surgery Journal, 2026)
Background: Resurfacing soft tissue defects in the distal foot remains challenging. Traditional options include amputation, cross-leg flaps, free tissue transfer, and skin grafts, each with limitations. The dorsal metatarsal artery perforator flap offers a safe, reliable alternative with minimal donor site morbidity, particularly suited for small to moderate defects. The aim of the study was to evaluate outcomes of the dorsal metatarsal artery perforator flap for reconstruction of distal dorsal foot and toe defects. Methods: This prospective observational study was conducted in the Department of Plastic Surgery, Dhaka Medical College Hospital, involving 30 patients selected by purposive sampling. All patients were followed for 30 days postoperatively. Results: Mean defect dimensions were 3.52±0.95 cm (length) and 2.52±0.56 cm (width), with a mean area of 9.07±3.83 cm². Mean flap dimensions were 5.6±1.33 cm (length) and 3.15±0.56 cm (width), mean area 17.89±6.07 cm². The first dorsal metatarsal artery perforator was used in 73.3% of patients, the second and third in 13.3% each. Marginal flap necrosis occurred in 46.7%, significant flap loss in 13.3%, and no necrosis in 20%. Venous congestion was seen in 53.3% and wound infection in 23.3%. No donor site morbidity was observed in 83.3%. Outcomes were satisfactory in 63.3%, good in 16.7%, and poor in 20% of cases. Conclusions: The dorsal metatarsal artery perforator flap provides satisfactory, durable coverage for soft tissue defects of the distal dorsal foot and toes with low donor site morbidity.